The Body Image and its Relation with Life Orientation among Sample of University Students Married and Unmarried - Fattah Abdel, Walaa Ahmed (Journal of Educational and Psychological Sciences, 2019)
The body image affects the individual's interactions and attitudes in life, and contributes to the composition of his experiences and trends through the events and positions. The present study aimed to reveal the relationship between body image and life orientation, and to know the differences between married and unmarried in both variables, where the researcher apply the scale of body image prepared by Shukir (2002), and the scale of life orientation prepared by Al-Ansari (2002), on a sample of 381 representing 27.3% of the total female students in the departments Special Education, Kindergartens, Home Economics, Islamic Studies from the faculty of education in Wadi Aldawasir, Prince Sattam bin Abdulaziz University, in the second semester of the academic year 2016/2017. The results showed a positive life orientation and a positive body image in the study sample, the results also showed positive correlation between body image and life orientation, while the results did not show differences between the study sample in body image and life orientation attributed to marital status.
Keywords: self-concept; body image disorder; optimism; disorder